Self-awareness as a predictor of academic burnout among vocational high school students - Elfiya Khoirunisa; Berliana Henu Cahyani; Andreas Yudha Fery Nugroho (Empathy : Jurnal Fakultas Psikologi, 2026)
Academic burnout has emerged as a significant mental health concern among students, particularly vocational high school students who are required to cope with both academic demands and practical learning activities simultaneously. Self-awareness is considered a protective psychological factor that enables individuals to recognize and understand their emotions, thoughts, strengths, and limitations when dealing with academic pressures. However, empirical evidence regarding the relationship between self-awareness and academic burnout among vocational high school students remains limited. This study aimed to examine the association between self-awareness and academic burnout among vocational high school students. A quantitative correlational design was employed involving 112 tenth-grade students from a vocational high school in Yogyakarta, Indonesia. Participants were selected using purposive sampling based on predefined inclusion criteria. Data were collected using self-awareness and academic burnout scales that demonstrated satisfactory validity and reliability. Spearman’s rho correlation analysis was performed because the data did not fully satisfy the assumption of normality. The findings revealed a significant negative relationship between self-awareness and academic burnout (ρ = −.56, p < .001), indicating that students with higher levels of self-awareness tended to report lower levels of academic burnout. The magnitude of the correlation suggests that self-awareness serves as an important protective psychological factor in coping with academic demands. These findings extend the literature on the role of self-awareness in vocational education settings and provide practical implications for developing self-awareness-based interventions to promote adolescent mental health and prevent academic burnout among vocational high school students.